1998
DOI: 10.1080/10408699891274255
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of β-Carotene from Carrots

Abstract: Beta-carotene acts as a pro-vitamin A or anti-cancer compound. Carrots contain the highest amount of beta-carotene of common fruits and vegetables, but each year 25% of carrot production is lost in the U.S. during processing and storage, while, at the same time, the market demand increases. This article is a review of the most recent studies concerning beta-carotene retention in carrots during processing and storage. Reducing the water activity by adding some aw lowering ingredients results in poor shelf-life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 0 publications
4
63
1
4
Order By: Relevance
“…Enzyme extracted pigments remain bound with proteins through covalent bonding or weak interactions that prevents pigment oxidation [14]. The findings of this study are in line with the results found by Desobry et al [21] who stated the freeze drying as the most effective way of preserving carotenoids from the carrots. Park [22] reported that the freeze drying significantly reduced carotene degradation of carrot during storage.…”
Section: Resultssupporting
confidence: 82%
“…Enzyme extracted pigments remain bound with proteins through covalent bonding or weak interactions that prevents pigment oxidation [14]. The findings of this study are in line with the results found by Desobry et al [21] who stated the freeze drying as the most effective way of preserving carotenoids from the carrots. Park [22] reported that the freeze drying significantly reduced carotene degradation of carrot during storage.…”
Section: Resultssupporting
confidence: 82%
“…Storage of dried food products may bring more severe losses of nutrients and bioactive compounds than during the drying process itself [163,[182][183][184]. For example, Kaminski et al [185] observed a rapid degradation of carotenoids in freeze-dried carrots during storage.…”
Section: Health Benefits Of Functional Dehydrated Foodsmentioning
confidence: 99%
“…sativus) has the highest carotene content of any human foods (Desobry et al, 1998). Carotene, a source of provitamin A, may play a role in protecting the body from numerous diseases that are associated with oxidative stress and damage (Handelman, 2001), and it also has many non-antioxidant properties that a ect cellular signaling pathways, modify the expression of some genes and can act as inhibitors of regulatory enzymes (Stahl and Ale-Agha, 2002).…”
Section: Introductionmentioning
confidence: 99%